Pengaruh Ukuran Perusahaan, Transfer Pricing, dan Capital Intensity terhadap Tax Avoidance yang Terdaftar di BEI - Priyatno Priyatno; Ratih Qadarti Anjilni (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to determine the effect of company size, transfer pricing, and capital intensity on Tax avoidance. Data were taken from energy sector companies listed on the Indonesia Stock Exchange for the period 2019-2023. The research method used is quantitative with data analysis using panel data regression using eviews 13 software. Samples were taken from 88 companies using the purposive sampling method and 7 companies were obtained from 88 companies over a period of 5 years, thus obtaining 35 research sample units. The results of the analysis show that company size has a significant effect on Tax avoidance, while transfer pricing and capital intensity do not have a significant effect. These results are not in line with several previous studies.